WASTE HANDLING METHODS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A brief analysis of the activities of LLC "Shurtan Gas Chemical Complex" in the field of waste management is presented. The goals of the enterprise in the area and measures to achieve the target indicators are outlined.